2019
DOI: 10.5194/acp-19-4499-2019
|View full text |Cite
|
Sign up to set email alerts
|

Intra-regional transport of black carbon between the south edge of the North China Plain and central China during winter haze episodes

Abstract: Abstract. Black carbon (BC), which is formed from the incomplete combustion of fuel sources (mainly fossil fuel, biofuel and open biomass burning), is a chemically inert optical absorber in the atmosphere. It has significant impacts on global climate, regional air quality and human health. During transportation, its physical and chemical characteristics as well as its sources change dramatically. To investigate the properties of BC (i.e., mass concentration, sources and optical properties) during intra-regiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 83 publications
3
23
1
1
Order By: Relevance
“…Due to the specialized location of the YRMB as a regional air pollutant transport hub with subbasin topography (Fig. 1b), the regional transport of air pollutants driven by the cold air flows of the East Asian winter monsoon over the CEC can create a special source-receptor relationship between the source regions of haze pollution in the upstream and the downwind YRMB region (Zhong et al, 2019). However, there are unresolved questions regarding the meteorological processes involved in the regional transport of air pollutants and the patterns of regional transport over CEC that may contribute to the air pollution changes observed in the YRMB area.…”
mentioning
confidence: 99%
“…Due to the specialized location of the YRMB as a regional air pollutant transport hub with subbasin topography (Fig. 1b), the regional transport of air pollutants driven by the cold air flows of the East Asian winter monsoon over the CEC can create a special source-receptor relationship between the source regions of haze pollution in the upstream and the downwind YRMB region (Zhong et al, 2019). However, there are unresolved questions regarding the meteorological processes involved in the regional transport of air pollutants and the patterns of regional transport over CEC that may contribute to the air pollution changes observed in the YRMB area.…”
mentioning
confidence: 99%
“…1). As a regional pollutant transport hub with sub basin topography, Central China is a region of transportation-pollution characteristics affected by two reported transport pathways from the vast flatland in central eastern China (Yu et al, 2020) and from the NCP region (Zheng et al, 2019a). In combination with high anthropogenic emissions and secondary aerosol formation (Huang et al, 2020), Central China often suffers severe pollution episodes in winter caused by PM 2.5 (Gong et al, 2015;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This method can typically explain two different types of sources (e.g., fossil fuel versus biomass burning) that contribute to LAC light absorption, and the results are highly relied on the source-specific absorption Ångström exponent (AAE) used in models. However, owing to the lack of access to obtaining these AAE data, most studies applied empirical values reported in other literatures (e.g., Healy et al, 2017;Küpper et al, 2018;Zheng et al, 2019). This may lead to a large uncertainty to the results, because the source-specific AAEs are site-dependent variables and varies with fuel types and their burning efficiencies (Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%